Shape of boulders ejected from small lunar impact craters. (1st October 2017) - Li, Yuan; Basilevsky, A.T.; Xie, Minggang; Ip, Wing-Huen
Abstract: The shape of ejecta boulders from 7 lunar impact craters <1 km in diameter of known absolute age was measured to explore whether it correlates with the crater age and the boulder size. The boulders were mapped and then measured by rectangular fitting and the shape was represented by the axial ratio or aspect ratio ( A ) of the rectangle. The main conclusions from the analysis of our measurement results are: 1) the percentages of the number of boulders of studied craters decrease with the increase of the axial ratio. Most (∼90%) of the boulders have the axial ratio in the range of 1–2; no boulder with axial ratio larger than 4 was found. 2) the axial ratios of mare ejecta boulders decrease with their exposure time, whereas that for highland ones show unchanged trend. This difference may be probably due to target properties. 3) The shape of ejecta boulders are influenced by mechanical strength of bedrocks and space erosion. 4) surface peak stresses caused by thermal fatigue maybe play a significant erosion role in the shape of boulders of various diameter. Highlights: The shapes of ejecta boulders from small lunar craters are measured. The percentages of number of the ejecta boulders decrease with their elongation. The bedrock properties and space erosion influence the shape of ejecta boulders. Thermal fatigue maybe play a significant role in the shape of boulders of various diameters.